I-voting - opportunities and threats. Conditions for the effective implementation of Internet voting on the example of Switzerland and Estonia - Górny, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
The aim of the article is to present the opportunities and threats resulting from the implementation of voting via the Internet (i-voting) and to discuss the conditions for effective implementation of this alternative voting procedure on the example of Estonia and Switzerland. Estonia is the only country in the world where i-voting is widely used. In Switzerland, on the other hand, this voting method has been used most often, although its use has been suspended for several years due to legal, infrastructural and political problems. What are the conditions for successfully implementing Internet voting? The attempt to answer this research question was possible thanks to the use of the following research methods: comparative, formal-dogmatic, behavioral and modified historical method. The key conclusion is that the implementation of i-voting must be preceded by many years of political, legal, infrastructural and social activities, and that the created system must be as transparent as possible.

Celem artykułu jest przedstawienie szans i zagrożeń wynikających z realizacji głosowania przez Internet (i-voting) oraz omówienie warunków skutecznej realizacji tej alternatywnej procedury głosowania na przykładzie Estonii i Szwajcarii. Estonia jest jedynym krajem na świecie, w którym powszechnie stosuje się głosowanie i-głosowanie. Z drugiej strony w Szwajcarii ta metoda głosowania jest najczęściej stosowana, choć jej stosowanie zostało zawieszone na kilka lat ze względu na problemy prawne, infrastrukturalne i polityczne. Jakie są warunki skutecznego przeprowadzenia głosowania internetowego? Próba odpowiedzi na to pytanie badawcze była możliwa dzięki zastosowaniu metod badawczych: porównawczej, formalno-dogmatycznej, behawioralnej oraz zmodyfikowanej metody historycznej. Kluczowy wniosek jest taki, że wdrożenie internetowego głosowania musi być poprzedzone wieloletnimi działaniami politycznymi, prawnymi, infrastrukturalnymi i społecznymi, a tworzony system musi być jak najbardziej przejrzysty.
I-voting - szanse i zagrożenia. Warunki skutecznej realizacji głosowania internetowego na przykładzie Szwajcarii i Estonii
Keywords: i-voting; electronic voting; Estonia; Switzerland; e-democracy; suffrage; i-voting; głosowanie elektroniczne; Estonia; Szwajcaria; e-demokracja; prawo wyborcze